(untitled) (Communications in Computational Chemistry, 2025)
This study presents a detailed examination of enzyme-catalyzed pericyclic reactions, specifically focusing on the synthesis of spirotetronate (decatromicin), catalyzed by the Plol4 enzyme. Utilizing the QM/MM method, we have discovered that the Plol4 enzyme significantly reduces the energy barrier in the Diels-Alder (DA) reaction, demonstrating its effectiveness in facilitating complex chemical processes. Our analysis suggests that this reduction is partly due to the interaction between the substrate and active site residues within the enzyme, which prearranges the substrate in a manner conducive to the [4+2] cycloaddition. Moreover, we observed a notable shift in the DA reaction mechanism from a concerted approach within the gas phase to an asynchronous approach within the enzymatic environment. This finding highlights the unique role of Plol4 in altering reaction pathways and underscores the enzyme's potential in synthetic applications. Overall, this research provides valuable insights into the mechanisms of enzyme-catalyzed reactions and their implications for the synthesis of polycyclic compounds.